Perencanaan dan Pelaksanaan Pembelajaran Koperatif Tipe Investigasi Kelompok untuk Meningkatkan Efektivitas Pembelajaran Fisika Kelas X: Penelitian Tindakan Kelas - Efendi, Septian; Koto, Irwan (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2015)
Abstract This paper addresses how to plan and implement the Group Investigation (GI) in an attempt to enhance the efectiveness of physics learning. It reports research with 30 Year-10 high school students studying temperature and heat transfer, during which the researchers employed a participatory action research approach. The research tools used to achieve the research aim were the written test, observations of teacher and student activities. To assess the students’ performance, a written test was administered following the validity and realibility of item test. Of 24 items was tried out, 18 items were valid with Cronbach Alpha reliabilities > 0.70. The teacher roles in learning activities were evaluated by using the classroom observation protocols conducted by three observers with ICC coefficient varrying above 0.71 to below 0.54. The results suggest that the GI instructional strategy can contribute positively to the efectiveness of physics learning (1) in terms of students’ performance on the test, and (2) by adaptating stage 1 (identifying the topics) and stage 2 (planning the investigation). Keywords: Group investigation, the efectivenss of physics learning. Abstrak Penelitian ini bertujuan untuk meningkatkan efektifitas pembelajaran fisika di kelas Xd SMA Negeri 6 Kota Bengkulu melalui perencanaan dan pelaksanaan pembelajaran koperatif tipe investigasi kelompok. (GI) yang melibatkan 30 siswa dan tiga pengamat. Penelitian tindakan partisipatori dilaksanakan dengan indikator efektifitas pembelajaran adalah daya serap dan ketuntasan belajar. Instrumen penelitian terdiri dari tes hasil belajar serta lembar observasi guru dan siswa. Melalui analisis butir tes, 18 butir tes diketahui valid dengan koefisien Alpha Cronbach >0,70. Lembar observasi guru dan siswa digunakan untuk menentukan efektivitas pembelajaran dengan koefisien ICC antar tiga pengamat (0,54) siklus I dan koefisien ICC (0,71) siklus II. Validasi internal dilakukan melalui Triangulasi. Simpulan menunjukkan bahwa model pembelajaran GI dapat meningkatkan efektifitas pembelajaran fisika: (1) ditinjau daya serap dan ketuntasan belajar; dan (2) melalui modifikasi model pembelajaran koperatif tipe GI pada tahap menetapkan topik permasalahan (Tahap-1) dan merencanakan penyelidikan (Tahap-2). Kata-kata kunci: Investigasi kelompok, Efektivitas pembelajaran fisika.